Endometrial compaction can improve assisted reproductive technology outcomes in frozen-thawed embryo transfer cycles using hormone replacement therapy: A cross-sectional study - Shahrzad Moeinaddini; Saeideh Dashti; Zahra Amini Majomerd; Nooshin Hatamizadeh (International Journal of Reproductive BioMedicine)
Background: Endometrial compaction (EC) is an ultrasound evaluation method that may predict assisted reproductive technology outcomes. Objective: This study aimed to assess the impact of EC on assisted reproductive technology outcomes in frozen embryo transfer cycles with hormone replacement therapy.